When a child lives with atopic dermatitis: an integrative literature review on parental experience - Martis, Chiara; Levante, Annalisa; Lecciso, Flavia (Frontiers in Pediatrics, 2025)
This integrative literature review, conducted with a systematic approach, examined how a child’s atopic dermatitis affects parental functioning. Fifty-four studies have been reviewed, identifying the key impacts, including work absenteeism, reduced quality of life, increased distress, sleep deprivation, and challenges in parent-child relationships. These dimensions were grouped into three focuses: Parents as workers, individuals, and caregivers. The review found that atopic dermatitis often disrupts parents' careers, causes emotional strain, family burden, and sleep issues. Parent-child interactions may also be affected, potentially impacting the attachment bond. Overall, the findings highlighted the interconnected nature of parental experiences and stressed the need to consider all family members' perspectives. A systemic approach in clinical practice, policy, and research is crucial to better support parents managing their child's condition.